The comparison of maternal stress level during pregnancy between two groups of pregnancy outcomes in the COVID-19 pandemic - Farisya Nurliana Fatin; Gatut Hardianto; Dwi Izzati (Universitas Airlangga, 2023)
HIGHLIGHTS Maternal stress level during pregnancy in the COVID-19 pandemic had normal category. There was no difference of maternal stress level during pregnancy between good and adverse pregnancy outcomes in the COVID-19 pandemic. Other factors can influence maternal stress level during pregnancy in the COVID-19 pandemic. ABSTRACT Objective: This study analyzed the comparison of maternal stress levels during pregnancy between two groups of pregnancy outcomes in the COVID-19 pandemic at Koja Regional General Hospital, North Jakarta, Indonesia. Materials and Methods: A hospital-based analytic observational study conducted with a case-control approach, involving mothers giving birth in March-August 2022, aged 20–35, without disease histories such as hypertension, anemia, gestational diabetes mellitus, and tuberculosis. Two groups in this study had matched inclusion criteria, consisting of 24 respondents with adverse pregnancy outcomes in the case group and 34 respondents with good pregnancy outcomes in the control group. The sampling method used total population technique. Data were obtained from medical record and modification of Depression Anxiety Stress Scale (DASS42) questionnaire. Analysis of confounding variables used different tests and bivariate analysis using the Mann-Whitney test. Results: Respondent characteristics had no difference (p >0.05). Respondent distribution with normal levels in the control group (70.6%) was higher than in the case group (45.8%). The result of Mann-Whitney test was no different in maternal stress levels during pregnancy between the case and control groups with pregnancy outcomes in COVID-19 pandemic (p=0.102). Conclusion: Most maternal stress levels during pregnancy were in the normal category. There was no difference in maternal stress level during pregnancy between both groups in COVID-19 pandemic at Koja Regional General Hospital, North Jakarta, Indonesia.